Virtual autopsy in legal medicine: literature review and example of application on the mummified remains - Kružić, Ivana; Jerković, Ivan; Mihanović, Frane; Marušić, Ana; Anđelinović, Šimun; Bašić, Željana (Medicine, Law & Society, 2018)
The virtual autopsy and post-mortem imaging methods are relatively novel methods used in medicine to determine cause and manner of death. They can also be exceptionally useful in the process of identification. Although they have numerous advantages, they are still not implemented in practice to a sufficient extent because the methodology has not yet been validated, and studies that deal with legal and practical implications of those methods are relatively scarce. In this article we describe basic principles and advantages of the methodology, explore related legal and practical issues, and present a case of virtual autopsy in practice on the mummified remains of St. Ivan Olini from Church of St. Blaise in Vodnjan (Croatia). Virtualna obdukcija in postmortalna metoda slikanja sta relativno novi metodi v medicini za ugotovljanje vzroka in načina smrti. Izjemno koristni sta lahko tudi v procesu identifikacije. Kljub številnim prednostim pa se v praksi še vedno ne izvajata v zadovoljivem obsegu, ker metodologija še ni potrjena, študije, ki se ukvarjajo s pravnimi in praktičnimi posledicami teh metod, pa so redke. V tem članku so opisana temeljna načela in prednosti metodologije, preučevana so pravna in praktična vprašanja ter predstavljen primer virtualne obdukcije v praksi na mumificiranih ostankih sv. Ivana Olinija iz cerkve sv. Blaža v Vodnjanu (Hrvaška).